Crystallization and Component Properties of Polyamide 12 at Processing‐Relevant Cooling Conditions. Issue 4 (15th September 2016) - Fischer, Christopher; Seefried, Andreas; Drummer, Dietmar
Abstract : For semicrystalline thermoplastics, the temperature‐time behavior during cooling of the melt can significantly affect the formation of crystalline structures (e.g., spherulite sizes, the degree of crystallization, crystal modifications, etc.) and hence, the resulting global component properties. In this paper, the crystallization of polyamide 12 at different cooling rates as well as process‐based temperature‐time profiles during cooling were investigated analytically with fast scanning calorimetry. Furthermore, based on analytical results, foils were extruded at different cooling conditions and tested mechanically and tribologically. The analysis reveals differences of the crystal melting behavior for different cooling conditions which is likely to originate in two different polymorphs of polyamide 12, γ, and γ′. Furthermore, mechanical investigations carried out with the extruded foils show that parts produced at high supercooling have less stiffness than parts produced at low supercooling, probably due to differences in the crystalline structures. Regarding tribological parameters, no clear differences could be measured. POLYM. ENG. SCI., 57:450–457, 2017. © 2016 Society of Plastics Engineers